An Outline of an Ecumenical Environmental Ethic - Etieyibo, Edwin (The Trumpeter, 2011)
An ecumenical environmental ethic is grounded on some values, imperatives or principles of the world’s major religions. Its basic feature is that it prescribes standards of behavior that are appropriate for human relationship with the natural world. In this paper I provide an outline of such an ethic. I do this in two ways. Firstly, by comparing the Hindu, Judeo-Christian, and Buddhist views on the natural environment and human interaction with nature. Secondly, by presenting some of the common values, imperatives or principles that emerge from these religions with regards to human relationship with the natural world. Although this account of an ecumenical environmental ethic is incomplete I believe it provides the basis for further discussions of not just what a complete account of ecumenical environmental ethic will look like but what it has to offer in the overall debate of how best to deal with the various environmental problems confronting us today.